SOX9 protein is stabilized by TGF-β and regulates PAPSS2 mRNA expression in chondrocytes. Issue 2 (February 2017) - Chavez, R.D.; Coricor, G.; Perez, J.; Seo, H.-S.; Serra, R.
Summary: Objective: We previously identified 3′-phosphoadenosine 5′-phosphosulfate synthase 2 ( PAPSS2 ) as a transcriptional target of transforming growth factor β (TGF-β) in chondrocytes. PAPSS2 is required for proper sulfation of proteoglycans in cartilage. Defective sulfation in the matrix results in alterations in mechanical properties of the cartilage that would be expected to result in degeneration. The objective of this study was to identify factors that regulate PAPSS2 expression and compare to a known TGF-β responsive gene, proteoglycan 4/lubricin ( PRG4 ). In this study, TGF-β-mediated regulation of SOX9 was characterized, and the involvement of SOX9 in regulation of PAPSS2 mRNA was investigated. Design: Primary bovine articular chondrocytes grown in micromass culture and ATDC5 cells were used as the model system. Adenoviruses were used to express SOX9 and SMAD3. siRNA was used to knock-down Sox9 and Smad3 . Western blot and real-time quantitative RT-PCR (qPCR) were used to measure changes in protein and mRNA levels in response to treatment. Results: Over-expression of SOX9 was sufficient to up-regulate PAPSS2 mRNA. TGF-β treatment of SOX9-expressing cells resulted in enhanced up-regulation of PAPSS2 mRNA, suggesting that SOX9 cooperates with TGF-β signaling. Furthermore, Sox9 was required for full TGF-β-mediated induction of Papss2 . In contrast, PRG4 was regulated by SMAD3 but not SOX9. SOX9 protein levels were increased after treatment with TGF-β, although SOX9 mRNA was not. SOX9 protein was post-translationally stabilized after treatment with TGF-β. Conclusions: TGF-β stabilizes SOX9 protein, and SOX9 is sufficient and necessary for TGF-β-mediated regulation of PAPSS2 mRNA, providing a novel mechanism for TGF-β-mediated gene regulation in chondrocytes.